Immunosuppressive Effect of B7-H4 Pathway in a Murine Systemic Lupus Erythematosus Model - Xiao, Ze Xiu; Zheng, Xu; Hu, Li; Wang, Julie; Olsen, Nancy; Zheng, Song Guo (Frontiers in Immunology, 2017)
B7-H4, one of the co-stimulatory molecules of the B7 family, has been shown to play an important role in negatively regulating the adaptive immune response by inhibiting the proliferation, activation and cytokine production of T cells. In this study, we investigate the role of B7-H4 in development of systemic lupus erythematosus (SLE). We investigated a murine model of SLE using transfer of bone marrow derived dendritic cells that were incubated with activated syngeneic lymphocyte-derived DNA(ALD-DNA). The recipient mouse produced anti-ds-DNA antibodies as well as displayed splenomegaly and lymphadenopathy as shown by significantly increased weights, and the kidneys showed lupus-like pathological changes include urine protein and glomerulonephritis with hyperplasia in glomeruli and increased mesangial cells and vasculitis with perivascular cell infiltration, glomerular deposition of IgG and complement C3. We showed that B7-H4 deficiency in bone marrow-derived dendritic cells could cause greater production of anti-ds-DNA antibodies in transferred mice, and the lymph tissue swelling and the kidney lesions were also exacerbated with B7-H4 deficiency. Treatment with a B7-H4 antagonist antibody also aggravated the lupus model. Conversely, B7-H4 Ig alleviated the lupus manifestations. Therefore, we conclude that B7-H4 is a negative check point for the development of systemic lupus erythematosus in this murine model. These results suggest that this approach may have a clinical potential in treating human systemic lupus erythematosus.